Diseño de un sistema de incentivos para mejorar el desempeño laboral del call center BCP-Trujillo-2019 - Cordova Coronado, Andrea del Milagro (2021)
The purpose of this research is to design a system of work incentives to improve the work performance of the Call Center BCP - Trujillo., Is a pre-experimental study. The study has as variables the system of incentives and work performance. The technique that was used was the survey with the questionnaire instrument to determine the current situation of the company, which was applied to a sample of 30 people. Likewise, the investigation tried to verify the general hypothesis, through the results, obtaining that the design of a system of labor incentives positively improves the labor performance of the Call Center BCP - Trujillo Company.